The Role of Negative-Pressure Wound Therapy in Lower-Limb Reconstruction - Sirisena, Renita; Bellot, Gregory Lucien; Puhaindran, Mark Edward (Indian Journal of Plastic Surgery, 2019)
Negative-pressure wound therapy (NPWT) has gained increasing popularity among clinicians since its introduction in 1997 as a potential aid to wound healing. Multiple benefits of NPWT have since been proven in studies, including increase in granulation tissue formation, decrease in bacterial load, and the improved survival of flaps. With our increasing use and greater understanding of the tissue and cellular changes that occur in a wound treated with NPWT, our lower-limb reconstructive practice has also evolved. Although controversial, the definite timing for lower-limb reconstruction has stretched from 72 hours to longer than 2 weeks as NPWT contains the wound within a sterile, closed system. It has also shown to decrease the rate of infection in open tibia fractures. Previously, a large number of critical defects of the lower limb would require free tissue transfer for definitive reconstruction. NPWT has reduced this rate by more than 50% and has allowed for less complicated resurfacing procedures to be performed instead.
Keywords: lower-limb reconstruction; lower-limb trauma; negative-pressure wound therapy; tissue resurfacing